Comparative evaluation of antimicrobial efficacy of silver nanoparticles and 2% chlorhexidine gluconate when used alone and in combination assessed using agar diffusion method: An In vitro study - Seetharam Charannya; Dasarathan Duraivel; Krishnan Padminee; Saravanan Poorni; Cruz Nishanthine; Manali Ramakrishnan Srinivasan (Wolters Kluwer Medknow Publications, 2018)
Context: Silver nanoparticle (AgNP) is a potent antimicrobial that is widely used in several fields of medicine. Chlorhexidine (CHX) gluconate is a well-known agent used in dentistry to eliminate oral microbial flora. Aims: The aim of this study is to evaluate the efficacy of AgNPs, 2% CHX gluconate, and the combination of two solutions against endodontic pathogens such as Enterococcus faecalis, Klebsiella pneumoniae, and Candida albicans. These organisms are frequently found in the root canal space and their persistence may lead to endodontic failure. The synergistic effect of the two solutions has been evaluated in this study. The antibiotic gentamycin was taken as the control group. Settings and Design: Agar well diffusion method was used and minimum inhibitory concentration of AgNP was found to be 15 μg/mL. AgNPs were synthesized from the aqueous plant extract of Cassia roxburghii. The combination of CHX-AgNP solution was stirred together by a glass rod. The values were tabulated and subjected to statistical analysis using the SPSS software version 20. One-way ANOVA test was used to compare within the groups and between groups. The level of significance was set at 5%. Results: CHX-AgNP combined solution exhibited the highest efficacy in comparison to these solutions used alone. They showed the highest efficacy against C. albicans among the three organisms tested. Conclusion: The present study demonstrates the antimicrobial efficacy of a novel mixture of CHX-AgNP solution, and it may be developed as a promising antimicrobial agent against endodontic flora.